The Influence of Financial Accounting Learning, Fintech Payment and Lifestyle on Financial Behavior of Accounting Students - Setiani, Rina Lailatul Ayuk; Widiawati, Hestin Sri; Linawati, Linawati (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Objective: This research aims to determine the influence of learning financial accounting, fintech payment and lifestyle on student financial behavior. Research Method: In this research using associative quantitative methods. The population used in this research  amounted to 174 active students of the Accounting Study Program at Nusantara PGRI Kediri University. The sampling technique in this study used a non-probability method in the form of a purposive sampling technique. The samples obtained were 121 respondents. In this research, data analysis techniques were used using the Statistical Package for Science (SPSS) version 21 software. Research Finding: The results of this research stated that learning financial accounting, fintech payment and lifestyle has a positive and significant effect on financial behavior of accounting student. It is hoped that this research will enable students to manage finances well.